Efficient routing algorithm for improving the network performance in Internet of Things. Issue 2 (22nd June 2022) - Krishna, Akula Vijaya; Leema, A. Anny
In the recent years, many routing protocols have been developed for Internet of Things (IoT) which reduces the delay and network congestion. However, in some urgent situations, the transmission of urgent or priority packets to the destination with in the specified time are compulsory. The tradition routing methods explores all the paths from source to destination which leads to longer paths and doesn't guarantee the delivery of priority packets. This paper concentrates on developing the priority-based event detection routing scheme in IoT. This method analyses the arrival packets and forwards to the destination by finding the shortest path with queue difference. The priority packets which arrive at the priority queue having minimum deadline is selected. The regular packets are followed with their normal queue policy. The experimental results proved that proposed method achieved 34% less end to end delay and 26% high accuracy in throughput compared to the other existing algorithms.